Potential of coronary angiography in the assessment of cardiac complication risk during non-cardiac interventions - A. N. Sumin; A. V. Bezdenezhnykh; D. O. Evdokimov; S. V. Ivanov; G. V. Moiseenkov; O. L. Barbarash (Российский кардиологический журнал)
Aim. To study the prevalence of coronary atherosclerosis in patients referred to planned non-cardiac interventions of intermediate and high risk. Material and methods. This retrospective analysis included 397 medical histories of patients who underwent planned interventions on aorta, carotid arteries, and peripheral arteries, PA (341 men and 56 women; mean age 60,0±13,0 years). Carotid endarterectomy (CEA) was performed in 161 patients (40,6%); PA intervention in 160 (40,3%); and abdominal aortic reconstruction in 76 (19,1%). Comparisons were performed by coronary angiography (CAG) results and immediate intervention results. Results. According to the CAG data, coronary artery (CA) stenosis